Rainfall thresholds for landslide activity in Portugal: a state of the art - Zêzere, José (2017)
Rainfall is the most important physical process responsible for the landslide triggering in Portugal. Results obtained worldwide have shown that control of rainfall on landslides differs substantially depending upon landslide depth and kinematics and the affected material. Therefore, the critical rainfall conditions for failure are not the same for different types of landslides, and may be strongly influenced by regional geologic and geomorphologic conditions. Rapid debris flows are typically triggered by very intense showers concentrated in just a few hours, and shallow translational soil slips are usually triggered by intense precipitation falling within the 1–15 days long range. On the contrary, activity of deep-seated landslides of rotational, translational and complex types is related to periods of nearly constant rainfall, lasting from several weeks to several months. The different rainfall intensity–duration conditions are associated with different hydrologic mechanisms for slope failure. The generation of surface run-off and high peak discharges in first-order mountain catchments is a critical triggering mechanism for debris flows. The intense rainfall allows the rapid growth of pore water pressure and the drop of capillarity forces that sustain the apparent cohesion of thin soils. As a consequence, shallow soil slips occur within the soil material or at the contact with the underlying less permeable bedrock. Long lasting rainfall episodes enable the steady rise of the groundwater table and the development of positive pore water pressures into the soil. Consequently, deep-seated failures occur in relation to the reduction of shear strength of affected materials. In this work, we present the state of the art concerning the proposition of empirical rainfall thresholds in Portugal for different types of landslides observed in different zones of the country: the Lisbon region, the Douro Valley and the NW Mountains, and the Povoação Municipality in São Miguel Island (Azores). The empirical thresholds applied in Portugal are based on the identification of past landslide events and include (i) the computation of antecedent rainfall threshold defined by linear regression, (ii) the normalization of rainfall by the mean annual precipitation, (iii) the definition of lower limit and upper limit rainfall thresholds and (iv) the definition of combined rainfall thresholds, which integrates the rainfall event and the antecedent rainfall for different time periods.